(3bWQ GdSjd aj CeQ GdNjds - (3YeQ Hf QSdGf Hf fUjQ Hf UGdM GdcfGfj, GdYSbdGfj GdCUd, Ke GdHdbjfj GdeUQj GdTGaYj, CHh MaU, SQGL GdOjf,J (B805 (3g` s
(3ChdgG (B:s
(3CeG HYO agPG JUfja dWja ai GdNjd TeQJ ajg ddGNJUGQ GdPjd GbJUQJ ajg Ydi aUhd SHYI s
(3BNQgG (B:s
(3hCeG EPG cGfJ ddJLGQI aEfgG JLH ajgG GdRcGI hGdMeO ddg QH GdYGdejf s
(3hbO GNJUQg ef JCdja GdTQa GdOejGWi hCVGa Edjg CTjGA hQJHI Ydi SHYI aUhds
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B46 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B284s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1351s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs